2022
DOI: 10.2196/34303
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Physical Activity Intervention for Individuals With Spinal Cord Injury: Planning and Development Processes

Abstract: Background Interventions to support physical activity participation among individuals with spinal cord injury (SCI) are required given this population’s low levels of physical activity and extensive barriers to quality physical activity experiences. Objective This study aimed to develop a mobile health intervention, called SCI Step Together, to improve the quantity and quality of physical activity among individuals with SCI who walk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…[ 23 ]. The results of the present study showed that the levels of GAP43 and NF200 were significantly increased in the spinal cord tissues of rats after scaffold implantation, suggesting that the mechanism by which scaffold transplantation improves motor and neurological functions in the hind limbs of rats with SCI and promotes axonal regeneration may be associated with the upregulation of GAP43 and NF200 levels in the tissues at the site of spinal cord injury [ 24 , 25 ]. Furthermore, more pronounced alterations of GAP43 and NF200 levels in the CBD-NGF/PCL/GE scaffold group versus the PCL/GE scaffold group are indicative of the clinical value of NGF in the treatment of SCI.…”
Section: Discussionmentioning
confidence: 97%
“…[ 23 ]. The results of the present study showed that the levels of GAP43 and NF200 were significantly increased in the spinal cord tissues of rats after scaffold implantation, suggesting that the mechanism by which scaffold transplantation improves motor and neurological functions in the hind limbs of rats with SCI and promotes axonal regeneration may be associated with the upregulation of GAP43 and NF200 levels in the tissues at the site of spinal cord injury [ 24 , 25 ]. Furthermore, more pronounced alterations of GAP43 and NF200 levels in the CBD-NGF/PCL/GE scaffold group versus the PCL/GE scaffold group are indicative of the clinical value of NGF in the treatment of SCI.…”
Section: Discussionmentioning
confidence: 97%
“…This is further highlighted by our assessment using the ABACUS, devised-by McKay and colleagues (86). Critically, Lawrason and colleagues (31) stress that behaviour change interventions need to target one or more of these core components (i.e., capability, opportunity, motivation) to change behaviour.…”
Section: Discussionmentioning
confidence: 90%
“…Given that smartphones are ubiquitous, it is estimated that there are now 3.5 billion users worldwide (28), mHealth interventions appear to be a favourable tool to support physical activity in people with SCI (29). Nevertheless, limited studies have concentrated on mHealth interventions to encourage physical activity in adults with SCI (30,31).…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…Logic models are graphic depictions of the relationships between resources, activities, outcomes, and impacts of a program or a system. They have been used in a variety of settings, for example, to inform the development of interventions such as a rehabilitation service for youth with concussion [ 7 , 8 ], mobile health support for physical activity in people with spinal cord injuries [ 9 ], and digital self-management in inflammatory bowel disease [ 10 ]. They have been used to understand how digital health interventions for self-management might be used to facilitate effective behavior change [ 11 ], how to design a plan to transform a health care system [ 12 ], and to capture complexities in systematic and scoping reviews [ 13 ].…”
Section: Introductionmentioning
confidence: 99%